THE EFFECT OF PERSON JOB FIT AND TRAINING ON EMPLOYEE PERFORMANCE THROUGH JOB SATISFACTION AT PT. PLN (PERSERO) UP3 MAKASSAR UTARA - Khayrunnisa B Muhammadia; Nurdin Brasit; Sumardi Lasise (Hasanuddin Journal of Applied Business and Entrepreneurship, 2021)
Every company is required to always survive in the face of all challenges, both existing challenges, and challenges that will come. In facing challenges, it is necessary to use human resources who can improve performance in the implementation of work. This study aims to identify and analyze (1) the influence of person-job fit and training on job satisfaction and employee performance at PLN (Persero) UP3 Makassar Utara (2) Satisfaction with the performance of employees, (3) Person Job Fit and training to performance through satisfaction at PLN (Persero) UP3 Makassar Utara. Data collection techniques through questionnaires using Structural Equation Modeling (SEM) with a variance-based or component-based approach with Partial Least Square (PLS). In determining the samples used were 58 respondents. The results of the study found that (1) person-job fit and training have an effect on job satisfaction and employee performance (2) Job satisfaction has a positive and significant effect on employee performance (3) Job satisfaction cannot mediate the effect of person-job fit on employee performance (4) Satisfaction work cannot mediate the effect of training on employee performance.